2013
DOI: 10.1186/1746-6148-9-32
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic study on pradofloxacin in the dog – Comparison of serum analysis, ultrafiltration and tissue sampling after oral administration

Abstract: BackgroundPradofloxacin, a newly developed 8-cyano-fluoroquinolone, show enhanced activity against Gram-positive organisms and anaerobes to treat canine and feline bacterial infections. The purpose of this cross-over study was to measure the unbound drug concentration of pradofloxacin in the interstitial fluid (ISF) using ultrafiltration and to compare the kinetics of pradofloxacin in serum, ISF and tissue using enrofloxacin as reference.ResultsAfter oral administration of enrofloxacin (5 mg/kg) and pradofloxa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
(27 reference statements)
3
8
0
Order By: Relevance
“…A marked lag time for drug diffusion into ISF was noted; however, the interstitial concentrations persisted after plasma concentrations declined. We believe that this study and others cited above indicate that highly lipophilic drugs may pass to intracellular sites and then diffuse back to the ISF during the time that plasma concentrations decline. The tissue concentration thereby serves as a reservoir for prolonged drug concentrations in the ISF.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…A marked lag time for drug diffusion into ISF was noted; however, the interstitial concentrations persisted after plasma concentrations declined. We believe that this study and others cited above indicate that highly lipophilic drugs may pass to intracellular sites and then diffuse back to the ISF during the time that plasma concentrations decline. The tissue concentration thereby serves as a reservoir for prolonged drug concentrations in the ISF.…”
Section: Discussionsupporting
confidence: 70%
“…However, the penetration of minocycline into interstitial fluid was ~50%, as described by the ‘penetration factor’ for the oral dose (Table ), and thus higher than expected from the fraction unbound (34.2%) in plasma. This phenomenon is most probably due to high lipophilicity of minocycline and has also been noted with other drugs that are highly lipophilic . The T ½ in plasma after oral administration was ~4 h, while it was ~7 h in ISF.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Whilst no clear explanation for this finding was apparent, the authors suggested that correction of PK/PD indices to take into account the AMD free fraction only in tissues was not necessary, because the free drug concentration in tissue exceeded the free concentration in plasma. A similar conclusion was proposed in dogs for pradofloxacin (Hauschild et al., 2013). Bidgood and Papich (2005) also concluded that, for drugs with a moderate degree of plasma protein binding, such as marbofloxacin, enrofloxacin and ciprofloxacin in dogs (22, 35 and 18%, respectively), total (bound and unbound) plasma concentrations could be used to compute PK/PD indices such as f AUC/MIC.…”
Section: Free Drug Plasma Concentration Is a Relevant Predictor Of Bisupporting
confidence: 83%
“…Hauschild et al 25 also compared the concentrations of pradofloxacin in the ISF and plasma in dogs. They also used the ultrafiltration probe for collecting the ISF, and a delay was observed in the increase in paradofloxacin concentration in the ISF, although it was administered orally to dogs.…”
Section: Resultsmentioning
confidence: 99%